Settledness, Polarity and Mood in Spanish Complements - Mejías-Bikandi, Errapel (Borealis – An International Journal of Hispanic Linguistics, 2022)
The paper discusses the effects of mood on the availability of an existential interpretation of negative words such as nadie "nobody" in the complement of emotive factive predicates in Spanish. In these contexts, the subjunctive mood allows nadie to be interpreted as a non-negated existential quantified expression, ∃x, equivalent to alguien. On the other hand, the indicative mood allows only for a negative universal interpretation of the expression, ∀x¬, or a negated existential interpretation, ¬∃x. An account of this phenomenon is proposed in terms of the notion of settledness. A proposition expressed by an indicative complement is asserted, which indicates the speaker's intention that it be settled in the context set. The proposition is grammatically settled. A proposition in the subjunctive mood is not asserted, the speaker is not indicating an intention that it be settled, it is in a grammatically unsettled state (p/¬p: a state in which p and ¬p are left undetermined). The word nadie is analyzed as denoting a quantity scale <∀, ∃>. Within an asserted complement, the interpretation of nadie is fixed at the highest, most informative, point in the scale, ∀. On the other hand, within the grammatically unsettled complement of an affective predicate, the interpretation of nadie is not fixed at the highest point in the scale. This indeterminacy allows it to assume a value at the lowest point, ∃. It is noted that this possibility provides an expressive tool which may be used to add an emphatic hue to an utterance.